THE VIEW OF FAMILY MEMORY IN THE MOVIE COMING HOME (2014) - Aulia Meidiska; Nurni Wahyu Wuryandari (Universitas Nasional, 2023)
This paper explores the view of family memory in the movie Coming Home (2014) to underline the importance of family memory in maintaining the family wholeness. This paper is a qualitative study with sociological approach focusing on the concept of family memory by Halbwachs. The results of this paper demonstrate that the presence of family memories determines one’s perception and action toward other family members and helps family members to encounter challenges that occur within the family or in the society. Meanwhile, the absence of family memory makes someone care less to other family members and get easily influenced by external factors outside the family. Family memory is concurrently possible to maintain cultural tradition within a family and even a nation, thus family memory between family members goes beyond family affair, not only strengthen and unite a family but also a nation.